Distributed observer-based cooperative guidance with appointed impact time and collision avoidance. Issue 14 (September 2021) - Li, Guofei; Lü, Jinhu; Zhu, Guoliang; Liu, Kexin
Abstract: The problem of cooperative guidance is considered with appointed impact time and collision avoidance for the leader-following flight vehicles, which consist of one leader with the target seeker and the other seeker-less followers. A fixed-time convergent guidance law is presented for the leader to achieve appointed impact time. To guarantee the simultaneous arrival of all the flight vehicles, a cooperative guidance law is proposed to make the follower-leader ranges keep proportional consensus with the range-to-go of leader. A distributed observer is put forward for the followers to estimate the range-to-go of leader. Moreover, the collision avoidance can be reliably fulfilled by the collaborative action of the direction-based and distance-based means.